Consciousness and loneliness : theoria and praxis - Mijuskovic, Ben Lazare, (Value Inquiry Book Series, 2019)
Current research claims loneliness is passively caused by external conditions: environmental, cultural, situational, and even chemical imbalances in the brain and hence avoidable. In this book, the author argues that loneliness is actively constituted by acts of reflexive self-consciousness (Kant) and transcendent intentionality (Husserl) and is, therefore, unavoidable. This work employs a historical, conceptual, and interdisciplinary approach (philosophy, psychology, literature, sociology, et cetera) criticizing both psychoanalysis and neuroscience. The book pits materialism, mechanism, determinism, empiricism, phenomenalism, behaviorism, and the neurosciences against dualism, both subjective and objective idealism, rationalism, freedom, phenomenology, and existentialism. It offers a dynamic of loneliness, whose spontaneous subconscious sources undercuts the unconscious of Freud and the "computerism" of the neurosciences by challenging their claims to be predictive sciences.